TRAUMA OF DIMPLE, A TRANSGENDER, AS DEPICTED IN THE NOVEL NARCOPOLIS BY JEET THAYIL - CHAUDHARY, PARIDHI; AGRAWAL , SHUCHI (International Journal of Psychosocial Rehabilitation, 2020)
he writers in Indian fiction have by and large deployed the transgenders to be one of the main characters of the stories. This is an important technique to give voice to the third-gendered population as they are considered as ostracized from the main stream society for their differential and scandalous status and role in the society. Writers like Khushwant Singh, Anosh Irani, Jeet Thayil, etc. have tried to show the world from transgendered people’s lens to present a critique to the society which lets this minority group of people, who happen to be marginalized, live in shabby conditions on the peripheries of the society. This paper is an attempt to discuss the arena of old Bombay wherein opium dens were highly active and its impact on third-gendered people’s life like that of Dimple who have been given the responsibility to put forward her view-points and judge the societal atrocities which are unfair and hypocrite in many ways.